Los Otros Californios - Talamantes, Cesar (Mexico, 2011)
The film shows the life of famers in Southern Baja California, Mexico. The farmers live in remote and isolated parts of the desert and must now face changes in their daily reality.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films